A novel authoring tool for augmented books - Gazcón, Nicolás Fernando (2014)
Augmented Reality (AR) has been studied from di erent application elds since the early 60s. Different research works in the educational field have been recently conducted, particularly based on a versatile AR application called Augmented Book. This paper focuses on a novel authoring tool for this kind of books. Our approach allows the possibility of adding virtual contents to any existing printed book. The application was implemented following a framework-based approach, making easy to extend with new features. Informal evaluations and observations by academics of different elds were conducted obtaining promising results.